Food Preference, Fecundity, Proximate Analysis on Eggs and Meat of Turbo crassus (W. Wood 1828) and Turbo setosus (Gmelin 1791) in Sepanjang Beach, Gunungkidul, Special Region of Yogyakarta - Rijal Romolo; Izzatul Auliya'; Trijoko Trijoko (Journal of Tropical Biodiversity and Biotechnology, 2021)
Turbo snails have important roles in the ecosystem as prey for predators, and decomposition of dead objects, and it is starting to decrease. This is quite worrying so that conservation efforts must be carried out immediately. Turbo snail species found in Sepanjang Beach, Gunungkidul are Turbo crassus and Turbo setosus. The aims of this study were to determine food preferences, the relationship between body size and fecundity, analyze egg quality based on proximate levels of the two species, and meat proximate of T. crassus and T. setosus. Samples were taken from Sepanjang Beach, Gunungkidul. Food preference was observed using the sedgwick rafter, fecundity was counted using the gravimetric method. Moisture content, protein content, fat content, ash, and carbohydrate content of both species eggs and meat were determined with proximate analysis at the UGM Central Laboratory for Food and Nutrition Studies. The results showed that the dominant food for T. setosus was Phaeophyta, whereas the dominant food for T. crassus was Microcoleus sp. and Phaeophyta. The fecundity of both Turbo species is exponentially positively correlated with all body sizes. Proximate analysis showed that the levels of fat and protein in the eggs of both species were quite high, which meant that the eggs are in good quality. The conclusion of this study is both species have slightly different food preferences. The fecundity of both species will increase exponentially with increasing body size and the broodstock of T. crassus and T. setosus Sepanjang Beach has good quality.